INOVASI PEMBELAJARAN DIGITAL MENGGUNAKAN MODEL POE PADA MATA KULIAH JURNALISTIK DI PRODI PBSI UNIVERSITAS MURIA KUDUS - dan Muhammad Noor Ahsin, Mila Roysa (Sasando, 2020)
Improving the quality of learning should be carried out by educators in this case as a driving force for the learning process to optimize education in accordance with the times. Covid-19 outbreak has brought changes to all levels of society, especially in the world of education. This is the background of learning innovation through the POE model in the Journalism course in the Indonesian Language and Literature Education Study Program, Faculty of Teacher Training and Education, Muria Kudus University. Through learning innovation by combining the POE learning model with the use of an online website application through the Jomla program, it will benefit the students of Indonesian Language and Literature Study Program Muria Kudus University because journalism learning is more systemized and more organized because it is packaged in an application. In addition, students are more enthusiastic and motivated, from the process of starting to look for actual news to processing news by uploading them to the online system website through the Jomla application, making students more creative with their work so as to increase learning outcomes in journalism subjects.